Leitura e interpretação do gênero artigo de opinião: uma experiência reflexiva em ambiente socioeducativo : Fundação C.A.S.A - Manhani, Ana Beatriz [UNESP] (2015)
Through the reading and knowledge, the human being is able to transform and modify the environment in which it is inserted, and live experiences through a dialogic reading and significant. The readings are worked with the aim of promoting a reflection and an interaction between the interlocutor, the reader and the text, making the significant texts and allowing the student the internal constitution of ethical and moral values, seeking to develop their awareness and critical spirit in relation to their rights and duties as citizens and helping them in their journey toward a new history of life in society. This research has as main objective will examine reader capacity and reflexive genre article of opinion and check dialogic, sociological and intertextually the work with the reading of examples of this kind in the classes of Portuguese language in a social and educational environment, in this case, the C.A.S.A Foundation (socioeductivo care center adolescentes). The development of a critical view of the student, their relationships with gifts speeches worked in the articles and the expansion of their communicative competence and consequently better exercise of citizenship, are the main issues discussed during the development of research. This research of the indicators proposed in the National Curricular Parameters for Portuguese Language, and is based on theories developed by authors who have proposed to study the text and genres thinking in Portuguese and reading instruction, among them we can mention, Elias; Koch (2006), Kleiman (2002), Leffa (1996), Marchuschi (2008), Solé (1998) and Todorov (1980). Other important references for the theoretical framework of this research are linked to Bakhtin Circle. From Bakhtin's theory, the teaching work stimulates the rebirth of participatory and critical student so that it can expose your opinion through speech and writing both in schools and in the...